2017
DOI: 10.1002/jclp.22510
|View full text |Cite
|
Sign up to set email alerts
|

Sex‐Positive Assessment and Treatment Among Female Trauma Survivors

Abstract: Sexuality and intimacy difficulties are often a part of the aftermath of sexual trauma. We argue that combining techniques from evidence‐based, trauma‐focused treatment with sex‐positive techniques used in sex therapy can best help survivors reduce trauma‐related symptoms and develop or regain comfort with their sexuality. In this article, we illustrate this approach by describing the case of a survivor of sexual assault, who completed 20 sessions of treatment that combined modules of trauma‐focused therapies,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 10 publications
1
10
0
Order By: Relevance
“…Consistent with research documenting an association between PTSD and sexual dysfunction (e.g., Baggett et al., ; Cosgrove et al., ; Yehuda et al., ), we observed that women with HSDD were more likely to meet criteria for current and lifetime diagnoses of PTSD when compared to sexually healthy controls. This finding is important as this study was the first to our knowledge to examine PTSD in relation to low sexual desire, specifically in women.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Consistent with research documenting an association between PTSD and sexual dysfunction (e.g., Baggett et al., ; Cosgrove et al., ; Yehuda et al., ), we observed that women with HSDD were more likely to meet criteria for current and lifetime diagnoses of PTSD when compared to sexually healthy controls. This finding is important as this study was the first to our knowledge to examine PTSD in relation to low sexual desire, specifically in women.…”
Section: Discussionsupporting
confidence: 90%
“…Although few studies have examined the associations among trauma exposure, posttraumatic stress disorder (PTSD), and low sexual desire in women specifically, several studies have implicated trauma exposure and PTSD as predictors of sexual difficulties in women (e.g., Baggett, Gonzalez-Rivas, Olson, Cameron, & Mona, 2017;Schnurr et al, 2009). As per the fourth edition of the Diagnostic and Statistical Manual for Mental Disorders (DSM-IV-TR; American Psychiatric Association [APA], 2000), an event is considered potentially traumatic if (a) it involves exposure to actual or threatened death or to serious injury or a threat to the physical integrity of self or others either via direct experience, witnessing, or being confronted (e.g., learning about in detail) with the event or events; and (b) the individual response involves fear, helplessness, and horror.…”
mentioning
confidence: 99%
“…Sex-positive therapists should create a comfortable environment where healthy sexuality can be acknowledged by the client, which may be very difficult for sexual minorities. This climate may encourage discussing intimate and personal topics and can promote positive outcomes in sexuality and intimacy [61].…”
Section: Discussionmentioning
confidence: 99%
“…The focus is primarily on the complexities of human interactions and thus not only on risks, deviance and pathology (Mosher, 2017). Being sexpositive means considering sexuality, including pleasure, as a natural, healthy and central part of human behaviour and well-being (Baggett et al, 2017;. It focuses both on the absence of physical and emotional harm and risk reduction, as well as on the presence of pleasure and meaningful experiences.…”
Section: Sex-positive Approachmentioning
confidence: 99%
“…A sex-positive approach is totally in accordance with the ethical principles of many professional associations (ACA, 2005;AMA, 1996;APA, 2010;NASW, 2008) as it recognizes and promotes the needs and choices of each individual (Williams et al, 2015), respecting basic values such as consent, free determination and access to sexual health. Some valuable examples of a clinical integration between the BPS model and the sex-positive approach were presented by Coleman et al (2018) regarding Impulsive/Compulsive Sexual Behaviour and by Baggett et al (2017) regarding trauma among sexual assault survivors. However, more work is needed to increase clinicians' comfort and motivation in addressing issues related to sexuality and demonstrating a more sex-positive perspective (Burnes et al, 2017).…”
Section: Clinical Practicementioning
confidence: 99%